The effects of varying doses of caffeine on cardiac parasympathetic reactivation following an acute bout of anaerobic exercise in recreational athletes - Amir Sarshin; Alireza Naderi; Carlos Janssen Gomes da Cruz; Foad Feizolahi; Scott C. Forbes; Darren G. Candow; Ebrahim Mohammadgholian; Mehrdad Amiri; Naghmeh Jafari; Alireza Rahimi; Eidi Alijani; Conrad P. Earnest (Taylor & Francis Group, 2020)
Background To examine the effects of varying doses of caffeine on autonomic reactivation following anaerobic exercise. Methods Recreationally active males (N = 20; 24 ± 2y) participated in a randomized, double-blind, placebo-controlled, crossover study where participants ingested: [1] Control (CON; no supplement), [2] a non-caffeinated placebo (PLA), [3] 3-mg∙kg− 1 of caffeine (CAF3) or [4] 6-mg∙kg− 1 of caffeine (CAF6) prior to Wingate testing. Parasympathetic (lnRMSSD, primary outcome) and global HRV (lnSDNN, secondary outcome) were assessed at rest (i.e., pre-ingestion), 45-min post-ingestion, and 5-min and 35-min post-exercise recovery. We used a GLM to assess mean (95% CI) changes from pre-ingestion baseline. Results Overall, we observed a significant trend for lnRMSSD and lnSDNN (both, p = 0.001, ηp2 = 0.745). Forty-five minutes after treatment ingestion, we observed a significant increase in lnRMSSD for CAF3 (0.15 ms, 95%CI, 0.07,0.24) and CAF6 (0.16 ms, 95%CI, 0.06,0.25), both being significant (both, p <  0.004) vs. CON (− 0.02 ms, 95%CI, − 0.09,0.04). Five-minutes after exercise, all treatments demonstrated significant declines in lnRMSSD vs. baseline (all, p <  0.001). After 35-min of recovery, lnRMSSD returned to a level not significantly different than baseline for CAF3 (0.03 ms, 95%CI, − 0.05, 0.12) and CAF6 (− 0.03 ms, 95%CI, − 0.17, 0.10), while PLA (− 0.16 ms, 95%CI, − 0.25, − 0.06) and CON (− 0.17 ms, 95%CI, − 0.28, − 0.07) treatments remained significantly depressed. A similar pattern was also observed for SDNN. Conclusion Caffeine ingestion increases resting cardiac autonomic modulation and accelerates post-exercise autonomic recovery after a bout of anaerobic exercise in recreationally active young men. However, no differences between caffeine doses on cardiac autonomic reactivity were observed.